2021
DOI: 10.3390/ijms22105248
|View full text |Cite
|
Sign up to set email alerts
|

Do Autism Spectrum and Autoimmune Disorders Share Predisposition Gene Signature Due to mTOR Signaling Pathway Controlling Expression?

Abstract: Autism spectrum disorder (ASD) is characterized by uncommon genetic heterogeneity and a high heritability concurrently. Most autoimmune disorders (AID), similarly to ASD, are characterized by impressive genetic heterogeneity and heritability. We conducted gene-set analyses and revealed that 584 out of 992 genes (59%) included in a new release of the SFARI Gene database and 439 out of 871 AID-associated genes (50%) could be attributed to one of four groups: 1. FMRP (fragile X mental retardation protein) target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…We have bioinformatically demonstrated that autism spectrum and autoimmune disorders do share predisposition gene signatures due to mTOR signaling pathway controlling expression. Our network analysis revealed that the great majority (up to 67%) of AID genes are related to the mTOR signaling pathway directly or indirectly [67]. Our bioinformatic analysis and reviewed published data allow us to hypothesize that both a certain part of ASD and AID comprise a connected set of disorders sharing a common aberrant pathway (mTOR signaling) rather than a vast set of different disorders.…”
Section: Mtor Signaling As a Key Player In Immune Microbiome And Beha...mentioning
confidence: 78%
See 1 more Smart Citation
“…We have bioinformatically demonstrated that autism spectrum and autoimmune disorders do share predisposition gene signatures due to mTOR signaling pathway controlling expression. Our network analysis revealed that the great majority (up to 67%) of AID genes are related to the mTOR signaling pathway directly or indirectly [67]. Our bioinformatic analysis and reviewed published data allow us to hypothesize that both a certain part of ASD and AID comprise a connected set of disorders sharing a common aberrant pathway (mTOR signaling) rather than a vast set of different disorders.…”
Section: Mtor Signaling As a Key Player In Immune Microbiome And Beha...mentioning
confidence: 78%
“…Our bioinformatic analysis and reviewed published data allow us to hypothesize that both a certain part of ASD and AID comprise a connected set of disorders sharing a common aberrant pathway (mTOR signaling) rather than a vast set of different disorders. Furthermore, a certain part of the autism spectrum might be a specific type of autoimmune disorder with an early manifestation of a unique set of predominantly behavioral symptoms [67].…”
Section: Mtor Signaling As a Key Player In Immune Microbiome And Beha...mentioning
confidence: 99%
“…Hence, Trifonova et al. proposed more attention should be paid on the mTOR signaling pathway for ASD investigation ( 22 , 43 ). Our results thereby strongly support this notion.…”
Section: Discussionmentioning
confidence: 99%
“…Gene network modeling was applied to study aggressive behavior pattern based on associative network reconstruction [34] using ANDSystem (Associative Network Discovery System), a tool for the automatic extraction of knowledge from scientific publications [35]. Ekaterina Trifonova and co-authors used gene network reconstruction to analyze role of mTOR signaling pathway in autism spectrum disorder (ASD) [36,37]. ASD is characterized by high genetic heterogeneity, as well as autoimmune disorders.…”
mentioning
confidence: 99%